The Interplay of Four Main Pathways Recomposes Immune Landscape in Primary and Metastatic Gastroenteropancreatic Neuroendocrine Tumors - Lou, Xin; Gao, Heli; Xu, Xiaowu; Ye, Zeng; Zhang, Wuhu; Wang, Fei; Chen, Jie; Zhang, Yue; Chen, Xuemin; Qin, Yi; Yu, Xianjun; Ji, Shunrong (Frontiers in Oncology, 2022)
Background: The four major pathways in gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) including chromatin remodeling, DNA damage repair, activation of mTOR signaling, and telomere maintenance, were mediated by some critical molecules and constituted critical mechanisms of regulation in tumorigenesis. However, the interplay and potential roles of these pathways-related molecules in tumor microenvironment of primary and metastatic site remained unknown. Methods: We systematically evaluated mRNA expression of 34 molecules associated with the four pathways in 227 GEP‑NEN samples. We used an unsupervised clustering method to assign the samples into two expression patterns of pathways-related molecules. Subsequently, we explored the specific cell-related molecules especially immune and stromal cells using WGCNA method based on differentially expressed genes (DEGs) responsible for the different patterns of pathways-related molecules, which provided a new method to qualify the pathway-related subtypes of individual tumors, then the PC_Score and PI_Score scoring system also were constructed using obtained specific cell-related molecules. Results: We demonstrated the specific pathways-related molecules (SMARCA4, MLH1, TSC1, ATRX, and ATR) were associated with cytolytic activity. Then we identified the two distinct patterns of pathways-related molecules, which were characteristic with significantly distinct immune landscape. Using WGCNA, we also identified the fibroblasts-related molecules and immune-related molecules. Based on these specific markers, we identified four distinct pathways-related subtypes, characterized by immune and fibrotic enriched (I/FE), immune enriched (IE), fibrotic enriched (FE), immune and fibrotic desert (I/FD), of which I/FE was characteristic with highest PC_Score and PI_Score whereas the I/FD present the opposite trend. I/FE positively correlated with transcriptional metrics of T cell activation and immunosuppression. Furthermore, the I/FE marked tumor with increased T cell activation scores (T cell costimulation and APC costimulation). Importantly, the four distinct pathways-related subtypes weren’t conserved in different tumor sites, because the I/FE were lack in liver metastatic site even though the IE, FE, and I/FD also could be observed in metastatic site. Conclusions: Our study was the first to provide a comprehensive analysis of the four major pathways in GEP-NENs. We revealed the potential function of these pathways-related molecules in immune landscapes. Our founding indicated the primary and metastasis GEP-NENs had distinct antitumor phenotypes.